Right to hereditary portion: comparative legal analysis - Nukusheva, A.A. (Bulletin of the Karaganda University “Law Series”, 2020)
The principle of free testament is fundamental to the inheritance law of the Republic of Kazakhstan, the Russian Federation and some other countries. In accordance with this principle, any citizen can bequeath all his property to persons both included and not included in the circle of heirs under the law, that is, persons who are not his relatives. To ensure that a dependent relative of the testator is unable to work, a relative whom he did not mention in the testament, there is a hereditary portion. It serves as one of the mechanisms of legal protection, providing a guaranteed share of hereditary property. The relevance of the research topic is that the right to a hereditary portion is the only restriction on the freedom of the testament and applies only if the testator made a testament for all his property, but the heir having the right to the hereditary portion in it is not indicated. Such a restriction on the principle of testament freedom arises only as a measure of protection for an heir who is unable to independently provide for himself with livelihoods. The authors study the concept, size and procedure for the provision of a hereditary portion in the legislation of Kazakhstan, Russia and some other countries, as well as the problems that arise when enforcing the rules governing the investigated legal relationship.